Evaluation of the Program for Strengthening the Profile of Pancasila Students from the CIPP Model Perspective - Ningsih, Dewi Rahayu; Bakhri, Syaiful (Jawda: Journal of Islamic Education Management, 2024)
This research aims to determine the results of evaluating the context, input, process, output of the project program to strengthen the profile of Pancasila students at Nasima Middle School, Semarang. Nasima Junior High School in the implementation of P5 (Pancasila Student Profile Strengthening Project) is not escorted even though the driving school should be escorted by the government. The escort is not sustainable, and only given material. Furthermore, everything related to implementation is determined by the school. Because Basically, the independent curriculum is very depends on the characteristics of the education unit according to different characters. Well, the curriculum at that time accommodates that character. Including in determining the project of strengthening the student profile of Pancasila. In this research, the method used is descriptive qualitative. Using interview, observation and documentation data collection techniques. The data obtained was analyzed by data reduction, data presentation and drawing conclusions. Test the validity of the data using triangulation of sources and methods. The results of the research show that: 1) The results of the evaluation of the program context for the project to strengthen the profile of Pancasila students have been running, it can be seen from how three projects were prepared for one year, 2) The results of the evaluation of the program input for the project to strengthen the profile of Pancasila students have been running, it can be seen from the competence of the educators , 3) The results of the process evaluation regarding obstacles in the implementation of the project program to strengthen the profile of Pancasila students are already underway, which can be seen from the implementation of three projects, 4) The results of the product evaluation regarding the continuation of the project program to strengthen the profile of Pancasila students are already underway with a graphic increase in the results of student achievement. It is recommended that the program be continued with some improvements in terms of budget, activity management, and long-term oriented products. And for the government, the driving schools should also be escorted in the implementation of P5.